Loss of One or Two PATZ1 Alleles Has a Critical Role in the Progression of Thyroid Carcinomas Induced by the RET/PTC1 Oncogene - Monaco, Mario (Cancers (Basel), 2018)
POZ/BTB and AT-hook-containing zinc finger protein 1 (PATZ1) is an emerging cancer-related gene that is downregulated in different human malignancies, including thyroid cancer, where its levels gradually decrease going from papillary thyroid carcinomas (PTC) to poorly differentiated and undifferentiated highly aggressive anaplastic carcinomas (ATC). The restoration of PATZ1 expression in thyroid cancer cells reverted their malignant phenotype by inducing mesenchymal-to-epithelial transition, thus validating a tumor suppressor role for PATZ1 and suggesting its involvement in thyroid cancer progression. Here, we investigated the consequences of the homozygous and heterozygous loss of PATZ1 in the context of a mouse modeling of PTC, represented by mice carrying the RET/PTC1 oncogene under the thyroid specific control of the thyroglobulin promoter RET/PTC1 (RET/PTC1(TG)). The phenotypic analysis of RET/PTC1(TG) mice intercrossed with Patz1-knockout mice revealed that deficiency of both Patz1 alleles enhanced thyroid cancer incidence in RET/PTC1(TG) mice, but not the heterozygous knockout of the Patz1 gene. However, both RET/PTC1(TG);Patz1(+/−) and RET/PTC1(TG);Patz1(−/−) mice developed a more aggressive thyroid cancer phenotype—characterized by higher Ki-67 expression, presence of ATCs, and increased incidence of solid variants of PTC—than that shown by RET/PTC1(TG); Patz1(+/+) compound mice. These results confirm that PATZ1 downregulation has a critical role in thyroid carcinogenesis, showing that it cooperates with RET/PTC1 in thyroid cancer progression.